Heat-Labile Enterotoxin-Induced PERK-CHOP Pathway Activation Causes Intestinal Epithelial Cell Apoptosis - Lu, Xi (Front Cell Infect Microbiol, 2017)
Enterotoxigenic Escherichia coli (ETEC) is a leading cause of diarrhea among children and travelers in developing countries, and heat-labile enterotoxin (LT) is one of the most important virulence factors. The pathogenesis of and virulence factors associated with ETEC have been well-characterized; however, the extent to which ETEC damages host cells remains unclear. In this study, we found that LT could induce decreases in intestinal epithelial cell viability and induce apoptosis in a dose- and time- dependent manner in both HCT-8 and Caco-2 cells. We analyzed the expression profiles of apoptosis-related proteins via protein array technology and found that Bax, p-p53(S46), cleaved caspase-3, and TNFRI/TNFRSF1A expression levels were significantly up-regulated in wild-type ETEC- but not in ΔLT ETEC-infected HCT-8 cells. Bax is essential for endoplasmic reticulum (ER) stress-triggered apoptosis, and our RNAi experiments showed that the PERK-eIF2-CHOP pathway and reactive oxygen species (ROS) are also main participants in this process. LT-induced ROS generation was decreased in CHOP-knockdown HCT-8 cells compared to that in control cells. Moreover, pretreatment with the ROS inhibitor NAC down-regulated GRP78, CHOP, Bim, and cleaved caspase-3 expression, resulting in a reduction in the apoptosis rate from 36.2 to 20.3% in LT-treated HCT-8 cells. Furthermore, ROS inhibition also attenuated LT-induced apoptosis in the small intestinal mucosa in the ETEC-inoculation mouse model.